Spontaneous pneumothorax during laparoscopy-assisted Billroth-I gastrectomy -A case report- - Su-Man Cha; Yong-Hun Jung; Dae-Sung Kim; Hyun Kang; Chong-Wha Baek; Gill-Hoi Koo (Korean Journal of Anesthesiology, 2010)
Pneumothorax associated with a pneumoperitonium in laparoscopic surgery is rare but can cause life-threatening complications. A 62-year-old man was scheduled for a laparoscopy-assisted Billroth-I gastrectomy under general anesthesia. Approximately 70 minutes after insufflating carbon dioxide into the intraabdominal cavity at a pressure of 12 mmHg, the peak inspiratory pressure increased, while the oxygen saturation decreased. The pneumothorax of the left lung was evident on the intraoperative chest radiograph. The pneumothorax improved after inserting a catheter into the affected area. The cause of the pneumothorax was unknown but an anatomical defect is believed responsible. This report shows that pneumothorax developed under an intraabdominal pressure in the conventional safety range. Careful monitoring and immediate treatment is necessary to prevent the condition from worsening.